Does neurophobia exist among rehabilitation sciences students? A survey at Universiti Kebangsaan Malaysia - Nor Azlin Mohd Nordin,; Nur Amirah Ishak,; Nur Azura Azmi,; Chai, Siaw Chui; Fatimah Hani Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Neurophobia, defined as ‘the fear of neural sciences and neurology’ is reported among medical students, which threatened their performance in neurology course. This phenomenon has not been studied among rehabilitation sciences students despite the significance of neurology as an area for rehabilitation. In this study we aim to assess the perceptions of neurology course and the possibility of neurophobia existence among rehabilitation sciences students of Universiti Kebangsaan Malaysia (UKM). We also aimed to identify learning methods which are regarded as useful among the students. A survey using self-administered questionnaires was conducted among 73 students from School of Rehabilitation Sciences of the university. Questions in the questionnaire were adapted from previous studies, in which neurophobia was indicated by poor knowledge and low confidence level in managing neurology course. Results showed that the percentage of participants who perceived having good knowledge of neurology was significantly higher than the percentage who claimed of having poor knowledge level (90.4% versus 9.6%, p < 0.01). Similarly, the percentage of participants who claimed having high confidence to handle neurology cases was higher than the percentage who expressed lack of confidence (79.2% versus 20.8%, p = 0.03). However, neurology course was perceived as difficult by majority of the participants (78.1%) when compared to other courses. Majority of the participants (97.3%) perceived clinical teaching as a useful method of learning rehabilitation science courses including neurology followed by problem-based learning (90.4%). While limited exposure to neurology cases was claimed as the main reason to why neurology is difficult. In conclusion, although neurology is perceived as a difficult course among rehabilitation sciences students, the students did not report lack of knowledge and confidence in the course. This implies that neurophobia does not exist among UKM rehabilitation students. Enhancement of learning methods may assist in reducing the level of difficulty of neurology course among the students.